Pendidikan Sains Berbasis Spiritualitas dalam Persepektif Al-Qur'an - Zamakhsyari Zamakhsyari (Almarhalah | Jurnal Pendidikan Islam, 2017)
Throughout 2006, Indonesia was rocked by a phenomenal work by Dr. Masaru Emoto about the true power of water. In his book entitled The True Power of Water, Emoto managed to show scientifically the results of his research that when whispered or written good words and certain prayers turn into beautiful crystals that function as "Hado" for human health.The Qur'an, though, was created more than fourteen years ago as a human guideline for achieving the salvation of the world and the hereafter. This is proven by several discoveries, one of which is Dr. Masaru Emoto who succeeded in creating "Hado" as a scientific finding that uses water media. For Muslims, the belief in the miracles of the Qur'an given to mankind itself opens the eyes of the heart to continue to hold fast to the Qur'an. Besides the greatness of the Qur'an as a source of knowledge that can be proven based on in-depth study of scientific science.Thus, the Qur'an provides knowledge about the principles of science and education, which are always associated with knowledge of metaphysics, morality and spirituality. The human method in getting knowledge is very relative to get it, but all is done not apart from the source that is essential that is the source of knowledge from God Almighty. That way, this is what is in the education process.